An overview of clinical activities in Endo-ERN: the need for alignment of future network criteria. Issue 2 (August 2020) - de Vries, Friso; Bruin, Mees; Cersosimo, Angelica; van Beuzekom, Charlotte N; Ahmed, S Faisal; Peeters, Robin P; Biermasz, Nienke R; Hiort, Olaf; Pereira, Alberto M
Abstract : Objective: Given that volumes of patients and interventions are important criteria to qualify as a reference centre (RC) for the European Reference Network on Rare Endocrine Conditions (Endo-ERN), the present study aimed to evaluate the data that were reported in the original application against subsequent assessments of activity and review the criteria that may define RCs using two main thematic groups (MTGs): Pituitary and Thyroid, as examples. Methods: Review of content in application forms and continuous monitoring data and of a survey distributed to RCs. A list of 'key procedures' for the assessment of performance of RCs was composed with the help of the Pituitary and Thyroid MTG chairs. Results: In the original application, the number of undefined procedures ranged from 20 to 5500/year (Pituitary) and from 10 to 2700/year (phyroid) between applicants. In the survey, the number of key procedures per centre ranged from 18 to 150/year (Pituitary) and from 20 to 1376/year (Thyroid). The median numbers of new patients reported in the continuous monitoring program were comparable with the application and survey; however, some centres reported large variations. Conclusions: Monitoring of clinical activity in an ERN requires clear definitions that are optimally aligned with clinical practice, diagnosis registration, and hospital IT systems. This is a particular challenge in the rare disease field where the centre may also provide expert input in collaboration with local hospitals. Application of uniform definitions, in addition to condition-specific clinical benchmarks, which can include patient-reported- as well as clinician-reported outcome measures, is urgently needed to allow benchmarking of care across Endo-ERN.